2020
DOI: 10.2337/dbi20-0022
|View full text |Cite
|
Sign up to set email alerts
|

Managing Hyperglycemia in the COVID-19 Inflammatory Storm

Abstract: A novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (coronavirus disease 2019 [COVID-19]) is now at global pandemic levels causing significant morbidity and mortality. Patients with diabetes are particularly vulnerable and more likely to get severe complications when infected with this virus. Although the information continues to emerge, here we provide our perspective on initial outcomes observed in hospitalized patients with diabetes and the potential role played by the proinfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 24 publications
4
102
0
4
Order By: Relevance
“…Fasting glucose was recorded from standard morning fasting blood biochemistry. The median length of hospital stay for nonsurvivors in our cohort was 17 days (interquartile range [IQR] [14][15][16][17][18][19][20][21][22], and patients often suffered sepsis and multiple organ injury during the 2nd week after admission according to our observations and a recent report (5). These conditions resulted in dramatic increases in glucose.…”
Section: Fasting Blood Glucose Parameterssupporting
confidence: 54%
“…Fasting glucose was recorded from standard morning fasting blood biochemistry. The median length of hospital stay for nonsurvivors in our cohort was 17 days (interquartile range [IQR] [14][15][16][17][18][19][20][21][22], and patients often suffered sepsis and multiple organ injury during the 2nd week after admission according to our observations and a recent report (5). These conditions resulted in dramatic increases in glucose.…”
Section: Fasting Blood Glucose Parameterssupporting
confidence: 54%
“…Second, patients with a diagnosis of diabetes, either comorbid or newly diagnosed, with better controlled blood glucose levels had less severe COVID-19 pneumonia and lower mortality risk compared with those with poorly controlled blood glucose during hospitalisation [38]. This suggests that improving glucose control could be a critical measure to improve outcomes in patients with COVID-19 pneumonia and strongly supports the need for an algorithm for hyperglycaemia treatment, validated through a randomised clinical trial [39]. Third, intensity of diabetes treatment in patients with comorbid diabetes was associated with higher mortality risk.…”
Section: Discussionmentioning
confidence: 77%
“…The same was true for younger patients <50 years requiring prolonged hospital stay (five of 18, 27.7%). Patients with diabetes mellitus are known to have severe COVID-19 infection with adverse outcome; the infection itself can hinder effective glycaemic control, necessitating close monitoring and careful management in diabetic patients [10]. Several studies have found an association between diabetes and ARDS, CCU admission, and death in patients with COVID-19 [11,12].…”
Section: Discussionmentioning
confidence: 99%